PERTAMINA AND SAUDI ARAMCO JOINT VENTURE PROJECT OF REFINERY BUILDING IN INDONESIA AS INDONESIAN STRATEGY FOR ENERGY SECURITY - Dini Putri Saraswati; Arnaldi Nasrum (Prodi Ilmu Politik, 2022)
Indonesia’s demand for energy to maintain its industrial development has grown significantly. As a consequence, Jakarta needs new energy sources to support the shortage of diesel and gasoline as the main resources. Saudi Aramco has been a vital partner to fulfil the energy supply considering its source and production capacity. This paper will scrutinise the joint venture project between Indonesian oil company, Pertamina and Saudi Arabian oil company, Saudi Aramco as an Indonesian strategy to overcome its growing need for oil and pursue its energy security. This qualitative research will employ the concept of the International Joint Venture (IJV to examine the role of the government of Indonesia in the negotiation and Implementation process and the challenges in implementing the project.